Accuracy of self‐reported height, weight and waist circumference in a Japanese sample - Okamoto, N. (Obes Sci Pract, 2017)
OBJECTIVE: Inconsistent results have been found in prior studies investigating the accuracy of self‐reported waist circumference, and no study has investigated the validity of self‐reported waist circumference among Japanese individuals. This study used the diagnostic standard of metabolic syndrome to assess the accuracy of individual's self‐reported height, weight and waist circumference in a Japanese sample. METHODS: Study participants included 7,443 Japanese men and women aged 35–79 years. They participated in a cohort study's baseline survey between 2007 and 2011. Participants' height, weight and waist circumference were measured, and their body mass index was calculated. Self‐reported values were collected through a questionnaire before the examination. RESULTS: Strong correlations between measured and self‐reported values for height, weight and body mass index were detected. The correlation was lowest for waist circumference (men, 0.87; women, 0.73). Men significantly overestimated their waist circumference (mean difference, 0.8 cm), whereas women significantly underestimated theirs (mean difference, 5.1 cm). The sensitivity of self‐reported waist circumference using the cut‐off value of metabolic syndrome was 0.83 for men and 0.57 for women. CONCLUSIONS: Due to systematic and random errors, the accuracy of self‐reported waist circumference was low. Therefore, waist circumference should be measured without relying on self‐reported values, particularly in the case of women.